2020
DOI: 10.3389/fmicb.2019.03016
|View full text |Cite
|
Sign up to set email alerts
|

Topical Therapeutic Efficacy of Ebselen Against Multidrug-Resistant Staphylococcus aureus LT-1 Targeting Thioredoxin Reductase

Abstract: As a thiol-dependent enzyme, thioredoxin reductase (TrxR) is a promising antibacterial drug target. Ebselen, an organo-selenium with well-characterized toxicology and pharmacology, was recently reported to have potent antibacterial activity against Staphylococcus aureus. In this paper, we demonstrated that ebselen has strong bactericidal activity against multidrug-resistant (MDR) S. aureus based on taking TrxR as a major target and disruption of the redox microenvironment. Further, the topical therapeutic effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…The strain was resistant to penicillin, cephalosporin, carbapenems, β‐lactamase inhibitors, aminoglycosides, quinolones, etc Its isolation demonstrated the universality of MDR UPEC in clinical settings, and it is urgent to develop new antibacterial strategies to fight against UPEC. In recent studies, we found out that ebselen and silver ion have potential antimicrobial activity against GSH‐positive bacteria, including MDR E coli and A baumannii 18,26,27 . In this study, the bactericidal activity against MDR UPEC BC1 of ebselen and silver ion was confirmed by visible spectrophotometry, transmission electron microscopy, DTNB assay and flow cytometry in vitro.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The strain was resistant to penicillin, cephalosporin, carbapenems, β‐lactamase inhibitors, aminoglycosides, quinolones, etc Its isolation demonstrated the universality of MDR UPEC in clinical settings, and it is urgent to develop new antibacterial strategies to fight against UPEC. In recent studies, we found out that ebselen and silver ion have potential antimicrobial activity against GSH‐positive bacteria, including MDR E coli and A baumannii 18,26,27 . In this study, the bactericidal activity against MDR UPEC BC1 of ebselen and silver ion was confirmed by visible spectrophotometry, transmission electron microscopy, DTNB assay and flow cytometry in vitro.…”
Section: Discussionsupporting
confidence: 58%
“…The activity of the untreated group was considered to be 100%. The protocols were performed as previously described 18,26,27 …”
Section: Methodsmentioning
confidence: 99%
“…In particular, there have been several strategies developed to block the antioxidant systems of bacterial pathogens [83]. For instance, the antioxidant compound Ebselen (also called PZ 51, DR3305, and SPI-1005; Figure 4B), is a synthetic organoselenium-based drug with anti-inflammatory, antioxidant, and cytoprotective activities [84,85]. Ebselen may have applications in the treatment of cardiovascular disease, arthritis, stroke, atherosclerosis, and cancer, by acting as a mimic of glutathione peroxidase in mammalian cells [86,87].…”
Section: Rons-producing Anti-infectives Are An Attractive Strategy Tomentioning
confidence: 99%
“…Ebselen may have applications in the treatment of cardiovascular disease, arthritis, stroke, atherosclerosis, and cancer, by acting as a mimic of glutathione peroxidase in mammalian cells [86,87]. However, Ebselen is also a potent inhibitor of TrxR in bacteria lacking glutathione, such as M. tuberculosis or S. aureus [88,89], which results in oxidative stress [85,90,91]. Importantly, Ebselen could also be combined with ROS-stimulating compounds that block the antioxidant defenses of bacteria such as silver nanoparticles (Figure 4 On the other hand, quinones ( Figure 4B) are compounds that can produce thiol-depletion in many prokaryotic organisms.…”
Section: Rons-producing Anti-infectives Are An Attractive Strategy Tomentioning
confidence: 99%
“…In two independent rodent studies, ebselen significantly reduced the burden of MRSA when applied topically to acute uncomplicated skin wounds [ 23 , 26 ]. In both rodent studies, treatment with topical ebselen resulted in a notable decrease in expression of proinflammatory cytokines including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1 beta (IL-1β) [ 23 , 26 ]. Furthermore, treatment with topical ebselen resulted in improved wound healing relative to the controls [ 23 ].…”
Section: Introductionmentioning
confidence: 99%